The B subunit of a rat heteromeric CCAAT-binding transcription factor shows a striking sequence identity with the yeast Hap2 transcription factor. - Maity, S N (1990)
CBF is a heteromeric mammalian transcription factor that binds to CCAAT sequences in a number of promoters such as the two type I collagen promoters, the albumin promoter, the major histocompatibility complex class II promoter, and others. It is composed of two components, A and B, that are both needed for DNA binding. We have isolated a rat cDNA containing the complete 341-amino acid coding sequence of the B component of CBF. Expression of this cDNA in vitro generates a polypeptide that shows the same dependency on the A component as the native B component in the formation of a complex with a CCAAT-containing DNA. The C-terminal portion of the B component from residue 260 to residue 312 shows a 75% sequence identity with a portion of the Hap2 protein, a component of a heteromeric CCAAT-binding protein in yeast. In contrast, the rest of the protein shows little sequence homology with Hap2, although both proteins contain glutamine-rich domains. In the B component of CBF this domain spans the amino-terminal 60% of the protein, whereas in Hap2 this domain is much smaller. Hence, only a few changes in one domain of this protein were tolerated during evolution between yeast and mammals, whereas the rest of the protein diverged much more extensively.